Case of internal jugular vein thrombosis and fever: Lemierre's syndrome or Trousseau's syndrome? - Meng-Yu Wu; Yueh-Tseng Hou; Jian-Yu Ke; Giou-Teng Yiang (Tzu Chi Medical Journal)
Internal jugular vein thrombosis is a rare critical cardiovascular emergency, which has potential catastrophic clinical outcomes by resulting in stroke and pulmonary embolism. Several etiologies have been reported; however, there are limited data on Lemierre's and Trousseau's syndromes, which are both rare conditions with advanced disease progression and poor clinical outcomes. Lemierre's syndrome may present with typical progressively infectious symptoms and signs, including sore throat, neck mass, and fever, whereas Trousseau's syndrome may present with thrombophlebitis and painful edema. Without antibiotic agents controlling the infection, the condition of patients with Lemierre's syndrome may progress to sepsis or septic shock. The infection pattern plays an important role for differential diagnosis. Herein, we describe the case of a 46-year-old woman presenting with atypical symptoms of Trousseau's syndrome mimicking Lemierre's syndrome. Laboratory analysis including protein C, protein S, rheumatoid factor, and antinuclear antibody ruled out hypercoagulopathy and autoimmune vasculitis. Abdominal computed tomography and panendoscopy revealed ulcerative tumor at the antrum. Pathological examination confirmed the presence of signet-ring cell adenocarcinoma. We highlight the clinical features and etiologies of internal jugular vein thrombosis, especially in Lemierre's syndrome and Trousseau's syndrome, to aid physicians in making an early diagnosis and providing timely management.